Creative cluster development governance, place-making and entrepreneurship - Komorowski, Marlen; Picone, Ike (Routledge, 2020)
"In recent decades, the importance of creative cluster development has gained increasing recognition from national and regional governments. Increasingly, governments have been investing in initiatives and urban development plans that aim to create or support localized creative industries. Our understanding of creative clusters is expanded with this insightful volume which looks at issues of governance, innovation and production. In addition to its theoretical contributions, the book also presents a rich range of international case studies, including co-working spaces in Toronto, business park development in MediaCityUK and Mediaclusters.Brussels and public-private partnerships in Warsaw. Creative Cluster Development will be valuable reading for advanced students, researchers and policymakers in urban planning, regional studies, economic geography innovation studies and the creative and cultural industries"--
Description based on online resource; title from digital title page (viewed on June 16, 2020)
Keywords: Business incubators; Cities and towns / Growth; Strategic alliances (Business) / Management; Business networks / Management; Cluster analysis